Remedicalizing cannabis : science, industry, and drug policy - Taylor, Suzanne (Research fellow) (Intoxicating histories, 2022)
"When cannabis tincture was withdrawn as a medical product in the UK in 1973, cannabis became regulated solely as an illicit drug. Within a decade cannabis-based drugs were back in the clinic. The UK is one of the biggest producers of medicinal cannabis, but few patients have access to these medicines. High-profile cases of parents campaigning for access to cannabis oil for severe and rare forms of epilepsy in their children are the most recent in a long line of controversies over cannabis and cannabis-based medicines. With mounting questions about patient access, the effectiveness of international drug control systems, and the role of expert advice, it is crucial to understand how we have arrived at this situation. While the historical literature has focused on cannabis as an illicit substance, Remedicalising Cannabis considers the botanical product and its potential to yield medical applications. Investigating the remedicalization of cannabis, Taylor explores the process whereby boundaries shift between illicit drug and licit medicine. Basing her arguments on archival material from expert committees, researchers, and activists and in-depth interviews with key players, Suzanne Taylor traces the issues and interests involved in this process, demonstrating the important roles of changing scientific knowledge, expert advice, industry, clinical trials, and patient activism. Remedicalising Cannabis investigates the evolving tensions that have brought us to the current situation and demonstrates the role of history in understanding today's debates about cannabis."--